THE GAIT OF THE FORUM LINGKAR PENA (FLP) IN REALIZING READING AND WRITING LITERACY IN THE SOUTH SUMATRA REGION - Yeni Mastuti (IKIP Siliwangi, 2022)
In the South Sumatra region, one of the organizations whose members are active in writing is Forum Lingkar Pena (FLP). It is interesting to research so that the work carried out by FLP can be an example for other literacy groups. The method used in this research is a descriptive qualitative method using a field research approach. Techiques of collecting data use observation instruments,interview and documentary. The results of this study indicate that in realizing literacy in literacy, FLP holds coaching classes specifically carried out by regions as well as by branches with various creative ideas. This routine activity presents competent writers through seminars, trainings and webinars. The use of print and electronic media to monitor members' works is also carried out. The factors that support the success of realizing literacy in literacy are because there are members who already have literacy skills before becoming members and there are also members who really make literacy a part of their life. Meanwhile, the inhibiting factors are the difficulty in coordinating with the board and members if the contact number is lost and the lack of priority for members to write.